MENINGKATKAN HASIL BELAJAR MATEMATIKA MELALUI MEDIA KANTONG BILANGAN KELAS II SDN KAIBON 03 - Cynthia Yoga Listiani; Endang Sri Maruti; Katmini (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
ABSTRACT Low student mathematics learning outcomes are one of the problems that need to be solved in elementary school students. This problem is caused by monotonous and less enjoyable learning and minimal use of learning media. This study aims to improve the learning outcomes of grade II students of SDN Kaibon 03 through the application of the Number Pocket media in mathematics subjects. This study is classroom action research (CAR) with a model developed by Kemmis & Taggart (1988) consisting of planning, action, observation, and reflection which took place in two cycles. The subjects of the study were 26 grade II students of SDN Kaibon 03. The data collection technique used observation techniques and evaluation tests which were carried out at the end of each cycle. The data analysis technique used quantitative and qualitative analysis techniques. Based on the data analysis that has been carried out, it can be concluded that the application of the Number Pocket media can improve mathematics learning outcomes in the material on the place value of numbers in grade II of SDN Kaibon 03. This can be seen from the percentage of completion of learning outcomes in the pre-cycle (31%), cycle I (53%), and cycle II (81%). This shows that by implementing the Number Pocket media, it can improve the mathematics learning outcomes of class II students at SDN Kaibon 03. Keywords: Number Pocket Media, Learning Outcomes, Mathematics ABSTRAK Rendahnya hasil belajar matematika siswa merupakan salah satu masalah yang perlu diselesaikan pada siswa di Sekolah Dasar (SD). Masalah tersebut dikarenakan pembelajaran yang monoton dan kurang menyenangkan serta minimnya penggunaan media pembelajaran. Penelitian ini bertujuan untuk meningkatkan hasil belajar siswa kelas II SDN Kaibon 03 melalui penerapan media Kantong Bilangan pada mata pelajaran matematika. Penelitian ini merupakan penelitian tindakan kelas (PTK) dengan model yang dikembangkan oleh Kemmis & Taggart (1988) yang terdiri dari perencanaan, tindakan, observasi, dan refleksi yang berlangsung sebanyak dua siklus. Subjek penelitian adalah siswa kelas II SDN Kaibon 03 berjumlah 26 siswa. Teknik pengumpulan data menggunakan teknik observasi dan tes evaluasi yang dilakukan setiap akhir siklus. Teknik analisis data menggunakan teknik analisis kuantitatif dan kualitatif. Berdasarkan analisis data yang telah dilakukan, dapat disimpulkan bahwa penerapan media Kantong Bilangan dapat meningkatkan hasil belajar matematika pada materi nilai tempat bilangan di kelas II SDN Kaibon 03. Hal tersebut dapat dilihat dari persentase ketuntasan hasil belajar pra siklus (31%), siklus I (53%), dan siklus II (81%). Hal ini menunjukkan bahwa dengan menerapkan media Kantong Bilangan mampu meningkatkan hasil belajar matematika siswa kelas II SDN Kaibon 03. Kata Kunci: Media Kantong Bilangan, Hasil Belajar, Matematika